1994
DOI: 10.1063/1.467000
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure branching ratios and translational energies of O(3P j) atoms produced from collision induced intersystem crossing of O(1D) atoms

Abstract: Collision induced intersystem crossing of O(2p 1D) to O(2p 3Pj) j=0,1,2 was studied by vacuum-ultraviolet laser induced fluorescence. The nascent j-branching ratios of O(3Pj) produced from collision of O(1D) with Xe, Kr, N2, CO2, and CF3H at the collision energy of 15.6, 14.7, 11.4, 13.0, and 14.4 kcal/mol are [O(3P0)]/[O(3P1)]/[O(3P2)]=(0.28±0.04)/(0.58±0.05)/1, (0.33±0.05)/(0.45±0.07)/1, (0.23±0.05)/(0.35±0.05)/1, (0.14±0.05)/(0.41±0.05)/1, and (0.20±0.05)/(0.45±0.05)/1, respectively. The j-branching ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 27 publications
4
31
1
Order By: Relevance
“…Under typical experimental conditions, all of the nascent O( 1 D) is converted to O( 3 P) in less than a microsecond – much faster than the vibrational energy transfer of interest. The O( 3 P J ) spin sublevels will exhibit a nearly statistical distribution following the quenching of O( 1 D) by the abundance of Xe [ Matsumi et al , 1994]. In the upper atmosphere, the sublevels are also likely thermalized at the local kinetic temperature due to the long O‐atom chemical lifetime.…”
Section: Methodsmentioning
confidence: 99%
“…Under typical experimental conditions, all of the nascent O( 1 D) is converted to O( 3 P) in less than a microsecond – much faster than the vibrational energy transfer of interest. The O( 3 P J ) spin sublevels will exhibit a nearly statistical distribution following the quenching of O( 1 D) by the abundance of Xe [ Matsumi et al , 1994]. In the upper atmosphere, the sublevels are also likely thermalized at the local kinetic temperature due to the long O‐atom chemical lifetime.…”
Section: Methodsmentioning
confidence: 99%
“…This value is consistent with a previous flow tube study which used a higher collision energy of 13.0 kcal/mol; by measuring the product O( 3 P 2 ) Doppler profile at 130.2 nm, it was found that 49Ϯ3% of the available energy was deposited into the product CO 2 . 23 The slow peak, with ͗E t ͘ϭ3.1 kcal/mol, was also fit with a broad P͑E͒. The maximum translational energy of this channel is 7.7 kcal/mol, equal to the collision energy.…”
Section: ͑R1͒mentioning
confidence: 99%
“…44 In reaction 13b, the distribution of spin-orbit states of the product S atom is expected to be statistical because the mechanism is likely similar to the reaction O( 1 D) + CO 2 in which the distribution in respective J states of O( 3 P J ) was reported to be nearly statistical. 45 If Similar to the procedures described for the reaction O ( 3 P) + OCS in Section A, the best fit spectrum was obtained with E* ) 30 000 ( 500 cm -1 , as shown in Figure 6. Trace a is a stick diagram of ∆V 3 ) -1 transitions calculated with the ν 1 /ν 2 polyad approximation, 14 and trace b represents the same distribution convoluted with fwhm ) 4 cm -1 ; the latter provides a practical comparison of vibrational distributions with experimental data.…”
Section: Infrared Emission From the O( 1 D) + Ocs Systemmentioning
confidence: 99%